Behavioristic Counseling Techniques for Mitigating Sexual Addiction Among Michat Application Users - Wahid, M. Wahid; Kusnadi, Kusnadi; Putra, Bela Janare; Sartika, Eka; Nurazhar, Ammar (Grief and Trauma, 2023)
This research is entitled The Application of Behaviorism in Reducing Sexual Addiction Among MiChat Application Users. The background of this study is based on the negative habit of an individual (client G) who frequently used the MiChat application to order sex workers in order to satisfy his sexual desires. The purpose of this research is to reduce client G's sexual addiction by applying behaviorist theory. The method used is a qualitative approach with data collected through observation, interviews, and documentation. The results showed that client G experienced significant behavioral changes in a positive direction. He was able to leave his negative habits through several behaviorist-based stages, including assessment, goal setting, motivation by companions, and implementation techniques such as delivering important advice, sincere repentance (Taubat Nasuha), deleting MiChat contacts, strengthening feelings of shame, and fostering positive thinking through self-suggestion. Evaluation was conducted regularly by the counselor by monitoring the client's openness and honesty during the counseling process. The study recommends that behaviorist approaches be applied consistently and combined with spiritual reinforcement to effectively address cases of sexual addiction.